THE ROLE OF EMOTIONAL INTELLIGENCE IN EDUCATIONAL LEADERSHIP: A COMPREHENSIVE REVIEW OF THE LITERATURE - Cynthia Petra Haumahu; Chamidatur Rohmah; Al-Amin (CV. ADIBA AISHA AMIRA, 2024)
Emotional intelligence has an influence on leadership effectiveness in the educational context. In educational leadership, emotional intelligence facilitates better interpersonal relationships, creates a positive learning environment, and enhances the ability to overcome challenges and make effective decisions. In addition, emotionally intelligent leaders can inspire and motivate staff and students, facilitate adaptation to change and promote innovation. Emotional intelligence is therefore a crucial element in developing effective and sustainable leadership in education